KOMPARASI KONSEP “TERAPI JIWA” IBNU QAYYIM AL JAUZYYAH DAN KAREN HORNEY - Amaliya, Risma Nailul; Achmad Khudori Soleh (An Natiq, 2024)
Soul therapy in the perspective of Sufism is defined as a process of purifying the soul which involves two main elements, namely tazkiyah (purification) of the soul from the negative traits that exist in every person and tahliyah (decorating the soul with positive traits). Characteristics. From this research is to compare the concept of mental therapy from Ibn-Qayyim Al-Jauziyyah and Karen Horney. This research method is qualitative based on a library research approach (qualitative research). The results of this study are (1) The concept of soul therapy from Ibn Qayyim Al-Jauziyyah, namely purification of a dirty soul with scientific therapy, tadzakkur and riyadha. (2) According to Karen Horney, the concept of mental health therapy that defines mental health disorders better known as neurosis arises from the following actions: Take time, reassess, practice paying attention, focus on relationships and speak as it is. Such mental disorders for treatment are born in a person who expects healing and can be accepted by the environment and if a person has a pure soul then he is closer to the Almighty so that his quality of life increases. Life will be higher.